Revealing Phosphorus Nitrides up to the Megabar Regime: Synthesis of α′‐P3N5, δ‐P3N5 and PN2. Issue 62 (2nd November 2022) - Laniel, Dominique; Trybel, Florian; Néri, Adrien; Yin, Yuqing; Aslandukov, Andrey; Fedotenko, Timofey; Khandarkhaeva, Saiana; Tasnádi, Ferenc; Chariton, Stella; Giacobbe, Carlotta; Lawrence‐Bright, Eleanor; Hanfland, Michael; et al.
Abstract: Invited for the cover of this issue are Dominique Laniel (University of Edinburgh), Florian Trybel (University of Linköping), and their colleagues. The image depicts a bridge built of the newly discovered δ‐P3 N5 solid with the structure featuring PN6 units, a previously missing connection between the carbon group elements nitrides and chalcogens nitrides. Read the full text of the article at 10.1002/chem.202201998 . Abstract : "We… found that there is a gap in our understanding of the crystal chemistry of pnictogen group elements nitrides" This and more about the story behind the front cover can be found in the article at 10.1002/chem.202201998 ).